2010
DOI: 10.1002/rcm.4597
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between isotope ratio infrared spectroscopy and isotope ratio mass spectrometry for the stable isotope analysis of plant and soil waters

Abstract: The use of isotope ratio infrared spectroscopy (IRIS) for the stable hydrogen and oxygen isotope analysis of water is increasing. While IRIS has many advantages over traditional isotope ratio mass spectrometry (IRMS), it may also be prone to errors that do not impact upon IRMS analyses. Of particular concern is the potential for contaminants in the water sample to interfere with the spectroscopy, thus leading to erroneous stable isotope data. Water extracted from plant and soil samples may often contain organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
246
4
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(267 citation statements)
references
References 64 publications
(132 reference statements)
13
246
4
4
Order By: Relevance
“…Extraction times may vary based on the soil type, e.g., clay vs. sand, and as such calibration should be performed for differing soil types. The system described here can also be used to extract water form plant material such as leaves and stems; however, some concern has been noted about the interference of organics that can co-distill with the water causing errors in the spectroscopic analysis of these water samples [14,15]. More recently, a study has shown that it is possible to calibrate the instrument for these types of contaminants and remove the interference from the measurement [16].…”
Section: Resultsmentioning
confidence: 99%
“…Extraction times may vary based on the soil type, e.g., clay vs. sand, and as such calibration should be performed for differing soil types. The system described here can also be used to extract water form plant material such as leaves and stems; however, some concern has been noted about the interference of organics that can co-distill with the water causing errors in the spectroscopic analysis of these water samples [14,15]. More recently, a study has shown that it is possible to calibrate the instrument for these types of contaminants and remove the interference from the measurement [16].…”
Section: Resultsmentioning
confidence: 99%
“…This new type of instruments does not usually require pretreatment and have precisions similar to traditional cryogenic based mass spectrometry methods (Lee et al, 2005;Wen et al, 2008;Wang et al, 2009d;Griffis et al, 2010). Recent research has indicated that plant derived volatile compound induced spectral contamination in leaf and stem water measurements could affect the accuracy of water stable isotopic compositions significantly (West et al, 2010;Zhao et al, 2011), limiting the application of spectroscopy-based method to plant sample measurements. There are studies which developed post correction method for modest spectral contamination of plant tissues (Schultz et al, 2011), but this remains a topic requiring further developments.…”
Section: Evapotranspiration Partitionmentioning
confidence: 99%
“…For this experiment the water was isotopically enriched using the partitioning effect caused by evaporation where light water, i.e., 16 2 H O will evaporate at a faster rate than heavy water, i.e., DH 16 O, 16 2 D O , DH 18 O, 18 2 D O , or 18 2 H O [6,7,16,26,27]. To accomplish this a 130-L plastic trashcan was filled with tap water from Lubbock, TX on 31 May 2012, and placed in a greenhouse and was allowed to enrich through evaporation over the course of 20 days.…”
Section: Isotopic Enrichment Of Source Watermentioning
confidence: 99%
“…Organic contaminants have been shown to cause spectral interference in water samples obtained by vacuum distillation of plant material [16][17][18]. However, the effects of these organic compounds can be evaluated and corrected using a procedure developed by Schultz et al [17].…”
Section: Calibration Of Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation